Observationally constrained surface mass balance of Larsen C ice shelf, Antarctica - Kuipers Munneke, P.; McGrath, D.; Medley, B.; Luckman, A.; Bevan, S.; Kulessa, B.; Jansen, D.; Booth, A.; Smeets, P.; Hubbard, B.; Ashmore, D.; Van den Broeke, M.; et al. (The Cryosphere, 2017)
This work is funded by the Netherland Polar Programme, Netherlands Earth System Science Centre (NESSC), NSF OPP research grant 0732946, NERC/GEF grants NE/L006707/1, NE/L005409/1, NE/E012914/1, GEF loans 863, 890, 1028. The surface mass balance (SMB) of the Larsen C ice shelf (LCIS), Antarctica, is poorly constrained due to a dearth of in situ observations. Combining several geophysical techniques, we reconstruct spatial and temporal patterns of SMB over the LCIS. Continuous time series of snow height (2.5–6 years) at five locations allow for multi-year estimates of seasonal and annual SMB over the LCIS. There is high interannual variability in SMB as well as spatial variability: in the north, SMB is 0.40 ± 0.06 to 0.41 ± 0.04 m w.e. year−1, while farther south, SMB is up to 0.50 ± 0.05 m w.e. year−1. This difference between north and south is corroborated by winter snow accumulation derived from an airborne radar survey from 2009, which showed an average snow thickness of 0.34 m w.e. north of 66° S, and 0.40 m w.e. south of 68° S. Analysis of ground-penetrating radar from several field campaigns allows for a longer-term perspective of spatial variations in SMB: a particularly strong and coherent reflection horizon below 25–44 m of water-equivalent ice and firn is observed in radargrams collected across the shelf. We propose that this horizon was formed synchronously across the ice shelf. Combining snow height observations, ground and airborne radar, and SMB output from a regional climate model yields a gridded estimate of SMB over the LCIS. It confirms that SMB increases from north to south, overprinted by a gradient of increasing SMB to the west, modulated in the west by föhn-induced sublimation. Previous observations show a strong decrease in firn air content toward the west, which we attribute to spatial patterns of melt, refreezing, and densification rather than SMB. Peer reviewed